Electrochemical study of hemin/polypyrole incorporated on carbon paste electrode for voltammetric ascorbic acid determination - ทองเทพ ภัทรานิตฐ์; มูลมั่งมี สมพร; พลเชี่ยว ฉัตรชัย (Progress in Applied Science and Technology, 2014)
This research, hemin/polypyrrole film was incorporated onto a carbon paste electrode by electro-deposition method. The modified electrode was electrochemical characterized in order to ascorbic acid determination. The hemin at electrode surface acts as the mediator to enhance electron transfer from ascorbic acid to an electrode. The anodic peak current observed in cyclic voltammetry was linearity dependent on the ascorbic acid concentration of 44 to 44,000 mg/L. The detection limit of the method is 0.5 mg/L. The developed method presents high accuracy, good precision and comfortable technique for ascorbic acid determination in various sample applications.